Plantae colombianae,-1: a new species of herrania from the putumayo (1942)
During the course of ethnobotanical investigation in the upper Putumayo in southern Colombia (*), the writer collected an interesting species of Herrania. Upon examination, this species proves to be undescribed. A description and critical comments relative to the relationships of this new species are herein presented together with a diagnostic drawingof the plant and its floral parts.